2022
DOI: 10.3390/rs14122933
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spatial Resolution on Satellite-Based PM2.5 Estimation: Implications for Health Assessment

Abstract: Satellite-based PM2.5 estimation has been widely used to assess health impact associated with PM2.5 exposure and might be affected by spatial resolutions of satellite input data, e.g., aerosol optical depth (AOD). Here, based on Multi-Angle Implementation of Atmospheric Correction (MAIAC) AOD in 2020 over the Yangtze River Delta (YRD) and three PM2.5 retrieval models, i.e., the mixed effects model (ME), the land-use regression model (LUR) and the Random Forest model (RF), we compare these model performances at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
0
0
1
Order By: Relevance
“…However, some studies are inconsistent with this finding. The effect of spatial resolution on satellite-based estimation of PM2.5 was analyzed by Bai et al [55]. Their results showed that the summer AOD-PM2.5 correlation decreased from 0.42 to 0.49 when the spatial resolution decreased from 3 km to 10 km.…”
Section: Comparison Of Different Spatial Resolutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies are inconsistent with this finding. The effect of spatial resolution on satellite-based estimation of PM2.5 was analyzed by Bai et al [55]. Their results showed that the summer AOD-PM2.5 correlation decreased from 0.42 to 0.49 when the spatial resolution decreased from 3 km to 10 km.…”
Section: Comparison Of Different Spatial Resolutionsmentioning
confidence: 99%
“…It was found that the performance started to improve with increasing spatial resolution until a maximum response was realized at 200 m, after which the performance decreased. The results in Bai et al [55] and Zheng et al [56] indicated that the performance of the model does not necessarily improve but may decrease as the spatial resolution increases.…”
Section: Comparison Of Different Spatial Resolutionsmentioning
confidence: 99%
“…PM having ≤2.5 µm of particle size in its diameter, known as PM 2.5 , has been reported as hazardous to human health by causing tuberculosis, lung cancer, and damage to the respiratory tract [1,2]. An increase in the short-term PM 2.5 is exemplary for human health, resulting in affected mortality rates negatively [3][4][5][6]. Different deleterious metals present in PM 2.5 affected the atmosphere, particularly in Asian countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…RF telah menjadi bidang penelitian yang populer karena mudah dipahami dan kuat [20]. Selain itu studi [21] menyatakan bahwa hasil validasi silang PM2.5 menunjukkan bahwa kinerja model tidak sensitif terhadap perubahan resolusi spasial untuk model LME dan LUR, sebaliknya model RF dapat membuat estimasi PM2.5 yang lebih akurat dengan resolusi spasial AOD yang lebih baik.…”
unclassified